2009
DOI: 10.1152/ajpheart.00747.2008
|View full text |Cite
|
Sign up to set email alerts
|

N-acetyl-seryl-aspartyl-lysyl-proline prevents cardiac remodeling and dysfunction induced by galectin-3, a mammalian adhesion/growth-regulatory lectin

Abstract: prevents cardiac remodeling and dysfunction induced by galectin-3, a mammalian adhesion/growth-regulatory lectin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
184
0
6

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(201 citation statements)
references
References 42 publications
6
184
0
6
Order By: Relevance
“…Fibrosis is generally considered to be vital for tissue repair, including cardiac and renal disease [19][20][21][22]. It has been reported that galectin-3 is produced by macrophages and activated myofibroblasts in experimental models of cardiac [23,24], renal [25,26] and liver fibrosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Fibrosis is generally considered to be vital for tissue repair, including cardiac and renal disease [19][20][21][22]. It has been reported that galectin-3 is produced by macrophages and activated myofibroblasts in experimental models of cardiac [23,24], renal [25,26] and liver fibrosis [27].…”
Section: Discussionmentioning
confidence: 99%
“…Given the observations that Gal-3 has a pivotal role in pathophysiology of adverse cardiac remodeling and it is an independent predictor of HF after ACS, it is reasonable to hypothesize that therapies inhibiting Gal-3 might influence HF progression in high-risk ACS patients [53,54] (Fig. 1).…”
Section: Gal-3 As Target For Therapeutic Strategiesmentioning
confidence: 99%
“…The first study to show that galectin-3 in the heart may be inhibited tested intrapericardial infusion of N-acetyl-serylaspartyl-lysyl-proline (Ac-SDKP), a naturally occurring peptide with anti-inflammatory and antifibrotic properties [31,32]. In this study, rats developed cardiac inflammation, fibrosis, and cardiac dysfunction after intrapericardial delivery of galectin-3; however, when AC-SDKP was administered concurrently with galectin-3, these harmful effects were abolished.…”
Section: Galectin-3 As a Therapeutic Targetmentioning
confidence: 88%